ASEAN+3 bond market guide 2017 Indonesia. (Metro Manila, Philippines Asian Development Bank, 2017)
The Indonesian bond market has seen significant changes in recent years, such as the reorganization of the regulatory framework of the capital and financial market with the creation of the Financial Services Authority (OJK).
Keywords: Financial institutions -- Indonesia; Money markets -- Indonesia; Electronic books